ADA APA DENGAN KOMUNIKASI ORANG TUA-REMAJA?: PENGARUHNYA TERHADAP AGRESIVITAS REMAJA PADA SESAMA - Berlianti, Diana; Vitalaya, Aida; Hastuti, Dwi; Sarwoprasojdo, Sarwititi; Krisnatuti, Diah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
There is a vague link between parent–adolescent communication and adolescents’ aggressiveness. Usually, the agressive perpetrators are the victims from their past experiences of abusive behavior from their surroundings. This present study aimed to examine influence among parent-adolescent communication pattern, parental physically and verbally harsh communication toward adolescents, parents-adolescents mutual avoidance, frequency of adolescents aggressivity toward others, and adolescents aggressiveness. Using Albert Bandura’s learning theoretical framework about violence messages reproduction, this study have been conducted using 367 adolescents sample of Bogor District and City. This report used quantitative and using cross sectional study design. Researcher also employed self-reported, survey methods in order to collect data. Result shown significant relation and influence among parental physically and verbally communication towards adolescents; parents-adolescents mutual avoidance; frequency of adolescents aggressivity toward others; and adolescents aggressiveness. Using Structural Equation Modelling (SEM) analyses, result proved that the victims of violence usually become perpetrators in future life.